The problem of reality - as one of the important reasons of marriage conflicts in the family. - Sitora , Ummatova (International Journal of Psychosocial Rehabilitation, 2020)
The article reveals the psychological essence of jealousy and its impact on emotional and interpersonal relationships. The psychological characteristics of the influence of jealousy on the person are described, the scientific and philosophical views of scientists on the types and signs of jealousy are given. The results of a study conducted among married couples are analyzed, with the help of which the issues of the influence of jealousy as one of the important reasons for the occurrence of married conflicts in interpersonal relationships are revealed.